2005
DOI: 10.1186/1471-2105-6-168
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput GoMiner, an 'industrial-strength' integrative gene ontology tool for interpretation of multiple-microarray experiments, with application to studies of Common Variable Immune Deficiency (CVID)

Abstract: Background: We previously developed GoMiner, an application that organizes lists of 'interesting' genes (for example, under-and overexpressed genes from a microarray experiment) for biological interpretation in the context of the Gene Ontology. The original version of GoMiner was oriented toward visualization and interpretation of the results from a single microarray (or other highthroughput experimental platform), using a graphical user interface. Although that version can be used to examine the results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(113 citation statements)
references
References 38 publications
0
113
0
Order By: Relevance
“…S5B in the supplemental material). Additionally, a gene ontology analysis using GoMiner (43) identified genes in the category of pathogenesis, including proteases (spl, ssp, and aur) and toxins, as the most highly enriched category of genes that are overexpressed in the ⌬sarA mutant, consistent with previous ⌬sarA mutant transcriptomics studies (60)(61)(62)(63). Interestingly, the ⌬sarA mutant is not the only NO˙-sensitive mutant we identified that overproduces proteases; the ⌬codY and ⌬rot mutants have also been characterized as overproducers of at least several of the 10 extracellular proteases secreted by S. aureus (64)(65)(66)(67)(68)(69).…”
Section: Resultsmentioning
confidence: 99%
“…S5B in the supplemental material). Additionally, a gene ontology analysis using GoMiner (43) identified genes in the category of pathogenesis, including proteases (spl, ssp, and aur) and toxins, as the most highly enriched category of genes that are overexpressed in the ⌬sarA mutant, consistent with previous ⌬sarA mutant transcriptomics studies (60)(61)(62)(63). Interestingly, the ⌬sarA mutant is not the only NO˙-sensitive mutant we identified that overproduces proteases; the ⌬codY and ⌬rot mutants have also been characterized as overproducers of at least several of the 10 extracellular proteases secreted by S. aureus (64)(65)(66)(67)(68)(69).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the biological pathways involved in human parturition, the set of proteins that changed during labour was mapped by GoMiner, using the whole genome as reference and limiting the analysis to the human database (Zeeberg et al 2005). A further pathway analysis was carried out through the use of IPA (Ingenuity Systems, www.ingenuity.…”
Section: In Silico Analysis Of Parturition Pathwaysmentioning
confidence: 99%
“…In our case, the false discovery rate was set to a stringent level of 5 per cent. Differentially exposed genes (DEGs) showing a fold change of two were further analysed with regard to their molecular functions, biological processes and biological pathways using information provided by Wormbase (www.wormbase.org) with high throughput GOMINER software (Zeeberg et al 2005). CATEGORIZER software was used to summarize gene ontology terms (Hu et al 2008).…”
Section: Microarray Data Analysismentioning
confidence: 99%